2017
DOI: 10.1097/md.0000000000008948
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous hemangiomas of the temporalis muscle with prominent formation of phleboliths

Abstract: Rationale:Hemangiomas are benign tumors characterized by an abnormal proliferation of blood vessels, most often occur in the skin and subcutaneous tissue, intramuscular hemangioma, a distinctive type of hemangioma within the skeletal muscle, account for <1% of all hemangiomas, temporalis muscle is a very uncommon site, cavernous hemangioma of the temporalis muscle with prominent formation of phleboliths is rare reported.Patient concerns:A 62-year-old man presented with a slowly increased mass in his right temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Pathologically, cavernous type of IMHs accounted for the majority and was expressed similar to venous malformations while the other 2 types were revealed as rich blood supply lesions. Most of the studies suggested that the imaging findings of oral and maxillofacial IMHs are consistent with venous malformations (6,(14)(15)(16)(17), and only a few studies indicated that the signal of IMHs lesions can be greatly enhanced (11,12); however, none of them neither has put forward the concept of rich blood supply status nor combined the enhancement with pathological types of IMHs for analysis. Through the comprehensive analysis of CT and MR images, we found that the capillary and mixed type of IMHs match with the characteristics of rich blood supply lesions, while cavernous IMHs were consistent with previous study results as relatively poor blood supply lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, cavernous type of IMHs accounted for the majority and was expressed similar to venous malformations while the other 2 types were revealed as rich blood supply lesions. Most of the studies suggested that the imaging findings of oral and maxillofacial IMHs are consistent with venous malformations (6,(14)(15)(16)(17), and only a few studies indicated that the signal of IMHs lesions can be greatly enhanced (11,12); however, none of them neither has put forward the concept of rich blood supply status nor combined the enhancement with pathological types of IMHs for analysis. Through the comprehensive analysis of CT and MR images, we found that the capillary and mixed type of IMHs match with the characteristics of rich blood supply lesions, while cavernous IMHs were consistent with previous study results as relatively poor blood supply lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Kalsiyum karbonat ve kalsiyum fosfat tuzlarının karışımından oluşan flebolit çekirdeği radyolojik olarak radyoopak ve radyolusent görünürler. Bu da lezyonun tipik soğan halkası benzeri görünümüne sebep olur 2,13,14 Histopatolojik olarak da radyolojisine benzer şekilde, konsantrik kalsifikasyonların yarattığı soğan halkası benzeri görüntüye rastlanır 4 . Benzer şekilde olgumuzda, radyolojik incelemelerde çoğunlukla hiperintens, yer yer hipointens alanlar içeren multipl kalsifiye nodüller izlendi.…”
Section: Discussionunclassified
“…The etiology of IMH is unknown, although trauma, abnormal embryonic tissue development, hormonal changes are considered predisposing factors in the growth of the IMH by stimulating more blood flow in the mass [ 3 , 4 ]. Initially, IMH clinically occur as a painless, slowly growing mass before making any noticeable symptoms [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…IMH is a vascular benign proliferation that mostly occur in the skeletal muscles of the lower limbs and rarely in the head and neck area [ 3 ]. The etiology of IMH is not clear yet, although trauma, abnormal embryonic tissue development, hormonal changes are considered predisposing factors in the growth of the intramuscular hemangioma by stimulating more blood flow in the mass [ 3 , 4 ]. Intramuscular hemangioma, usually manifested clinically as painless, slowly growing with clear boundaries of the mass, and the development of calcified thrombi, which known as phleboliths [ 5 ].…”
Section: Introductionmentioning
confidence: 99%